Answer:
B) (4x-5i)(4x+5i)
Step-by-step explanation:
The expression can be treated as the difference of squares, and factored accordingly. That factoring is ...
a² -b² = (a -b)(a +b)
__
Here, we have ...
a² -b² = 16x² -(-25)
a² = 16x² ⇒ a = 4x
b² = -25 ⇒ b = √-25 = 5i
Then the factoring is ...
(a -b)(a +b) = (4x -5i)(4x +5i)
Answer:
-2.3
Step-by-step explanation:
Answer:
The answer is B: 468.50
Step-by-step explanation:
Answer:
false a = -3
Step-by-step explanation:
7v^2 + 2v^3 -7v - (5v^3 -4v^2 +10v)
7v^2 + 2v^3 -7v - 5v^3 +4v^2 -10v
-3v^3 + 11v^2 -17v
Answer:
Qinghai
Step-by-step explanation: